FIRST REPORT OF DRAFT GENOME SEQUENCING FOR LIGILACTOBACILLUS SALIVARIUS SUAM7 FROM ORAL DISEASE PATIENTS IN IRAQ - Dawoud, Soher; Alrawi, Amera Mahmood (PT. Antis International Publisher, 2025)
Objective: The purpose of the present study is to examine the genomic composition of Ligilactobacillus salivarius SuAm7, emphasizing both its possible clinical significance and its function in oral health. Method: Gram-staining, 16S rRNA PCR and Whole-genome sequencing were used to identify and cultivate the saliva sample. Whole-genome sequencing with Illumina technology was done, followed by analysing the genome’s features and figuring out where it fits in the picture of evolution. Results: SuAm7’s genome was 1.84 Mb in total, smaller than most related species and it shared a lot of similarities with L. salivarius subsp. salicinius DSM 20554. Functional annotations indicate that genes for secondary metabolism, nitrogen usage, movement and chemotaxis were missing which suggests the mouth cavity is a place where the bacteria need to be specially adapted. The way the bacterium is classified was confirmed by genetic tests including ANI analysis and in silico DNA-DNA hybridization. Novelty: This article reports on the draught genome of Ligilactobacillus salivarius SuAm7, an oral bacterium from someone who was healthy in Iraq. The findings emphasise the value of L. salivarius SuAm7 in the oral microbiota and describe its genetic and how it functions. The study shows what types of bacteria are present in Iraqi people’s mouths and indicates that L. salivarius might be useful in fighting bad breath.